Developing risk management treatments for taro from the Pacific Islands - Jamieson, Lisa E.; Page-Weir, Natalie E.M.; Wilkinson, Reuben T.; Redpath, Simon P.; Hawthorne, Amanda J.; Brown, Samuel D.J.; Aalders, Lee T.; Tunupopo, Fa'alelei; Tugaga, Angelika; To'omata, Tanu; Shah, Farhat; Armstrong, Jack W.; et al. (New Zealand Plant Protection, 2018)
Most taro imported from the Pacific are currently fumigated with toxic methyl bromide to kill pests, predominantly mites and nematodes that are generally found on the surface of taro. Combined high-pressure washing (HPW) and hot water treatment (HWT) were examined as alternative methods for disinfesting taro. Taro mites (Rhizoglyphus sp.) and root knot nematodes (Meloidogyne sp.) were exposed to a range of HWT and HPW conditions separately or together. At 47?C, mean lethal times of 2.6—2.9 mins and 3.9—4.1 mins were estimated to control 99% and 99.99% of nymph and adult mites, respectively. Mite nymphs and adults were more tolerant to HWT than mite eggs. The mean lethal time estimate to control 99% of juvenile nematodes was 4.5 mins. Nematode eggs were the most tolerant life stage with only 10% mortality after a 4-min 47?C HWT. HPW+HWT reduced heavy infestations of mobile pests on taro (n=30—117/taro) by 100%. HPW followed by HWT 50?C for 12.5 mins reduced viable egg infestation by 95.8%. HPW followed by HWT can control surface pests on taro while maintaining taro quality.